A Case of Pelvic Schwannoma Presenting Prominent Eggshell-Like Calcification - Nakashima, Takaaki (Hindawi Publishing Corporation, 2013)
Pelvic schwannoma typically forms a large, well-circumscribed mass in the retroperitoneum or presacral area and frequently undergoes cystic degeneration. It appears as a well-demarcated round or oval mass, often showing prominent cystic degeneration and calcification. Characteristics of these calcifications are punctate, mottled, or curvilinear and are seen along the walls of the mass. Herein, we describe a case of schwannoma presenting a huge pelvic mass with unique eggshell-like calcification.